Trust the stars [large type] - Goyer, Tricia (Center Point Large Print, 2024)
"Olivia Garza thrives in her unconventional, service-oriented life. By day, she helps troubled teens in inner-city Little Rock . . . by night, she creates a viral web series when she tries to better understand her mother's desperate decisions by retracing her steps with a camera. So far, Olivia has always been the anonymous narrator, but she's promised to reveal herself in the last stop on her documentary: Kenya. Prince Louis, heir to the throne of the small European kingdom of Alloria, is in Kenya to run away from a broken heart -- and the media circus that comes with it. When he meets Olivia, they share a magical day on safari, but any dreams of happily ever after come crashing down with the flash of the paparazzi cameras, when Olivia realizes that he represents everything she most despises in the world. In World War II Rome, Princess Alessandra Appiani had her own life-changing choices to make. She could have chosen safety within the walls of the Vatican, but instead she risked her life to save Jewish children. When Olivia is hired to help create a documentary about Alessandra, learning about the sacrifice of a royal who goes from palace to prison forces her to face the hardest questions of all: Should she continue on the path she's carved for herself, or trust God to give her the future she never thought she wanted?"--